Decolorization and Transformation of Synthetic Dye Methylene Blue by Brown-Rot Fungus Fomitopsis pinicola - Adi Setyo Purnomo; Hamdan Dwi Rizqi; Aulia Ulfi; Refdinal Nawfa; Herdayanto Sulistyo Putro (Indonesian Journal of Chemistry, 2022)
Methylene blue (MB) is a synthetic dye widely used in industries that is difficult to degrade in the environment due to its stability. Brown-rot fungus Fomitopsis pinicola is an organism that is known to be able to degrade some organic pollutants such as DDT, aldrin, dieldrin, and methyl orange dye. This study aimed to explore the ability of F. pinicola on MB biodecolorization, to identify metabolites and propose a biodecolorization pathway. F. pinicola was evaluated for MB biodecolorization on PDA agar and PDB liquid media. The metabolites were determined by using LCTOF/MS. The PDA agar medium's largest index decolorization (ID) was 0.915%. The MB decolorization in liquid PDB medium showed the highest percentage of decolorization of 92.56% at MB concentration of 100 mg/L after 14-days incubation. The analysis using LC-TOF/MS showed metabolites from MB biodecolorization, namely 3-amino-7-(methylamino) phenothiazin-5-ium (Azure C), 3-(dimethylamino)-7-(methylamino) phenothiazin-5-ium (Azure B), and 3,7-bis(dimethylamino)-4aH-phenothiazin-5-one. The MB degradation pathway was proposed through demethylation and oxidation reactions based on the detected product metabolites. These results indicated that F. pinicola is a suitable agent for biodecolorization of MB, and can potentially be used for bioremediation of MB waste in the environment.